Pemberdayaan Sosial Ekonomi Masyarakat Desa Meuria Paloh Kota Lhokseumawe Melalui Pemahaman Teknologi Dan Sertifikasi Halal Menuju Penguatan Kawasan Agrowisata - Mukhlis; Musrizal; Mangkuwinata, Sonny Muhammad Ikhsan; Safrina, Emi; Yusrawati (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2023)
This service activity aims to increase community empowerment in the field of digital economy and Islamic sharia through understanding the use of technology and halal certification towards strengthening agro-tourism areas. This is certainly in line with the government's vision which continues to strive to encourage Indonesia to become a world producer of halal products. Halal certification, which was originally voluntary, has now changed to mandatory. The implementation of halal certification is carried out in stages starting with food and beverage products on 17 October 2019 and non-food products starting on 17 October 2021. Another aim is to develop synergy between universities and village communities so that training and mentoring are needed. The material presented is how to create an online buying and selling and promotional account and how to prepare a manual document for a halal guarantee system. The results of this service can be used as input for lecturers and education staff to increase professionalism and also as input in preparing further service proposals so that they are worthy of being funded by the Higher Education